ANALISIS LAPORAN REALISASI ANGGARAN UNTUK MENILAI TINGKAT EKONOMI, EFEKTIVITAS, DAN EFISIENSI KINERJA KEUANGAN BLUD - Fitria Syaifanur; Muhammad Saleh (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aim to provide the level of economy, efficiency and effectiveness of the financial performance of BLUD RSUD dr. Zainoel Abidin Banda Aceh. This study uses a quantitative method with a descriptive analysis approach. The author uses the Work Plan and Budget Realization Report documents used for this research by confirming that the Value For Money indicator is in accordance with the Minister of Finance Regulation number 214 of 2017. The object of this research is the BLUD RSUD dr. Zainoel Abidin Banda Aceh. The results of this study indicate the performance of the BLUD RSUD dr. Zainoel Abidin is still less economical and inefficient, but has been effective based on the Performance Measurement of the Minister of Finance Regulation number 214 of 2017.